Far-field thermal radiation properties of graphene under uniaxial strain. (26th October 2022) - Xie, Wen-Wu; Qian, Wen-Ri; Zhang, Yong-Mei
Abstract: Electronic band structure and optical conductivity of single-layer graphene could be altered by applied uniaxial strain. Valley and space inversion symmetries are broken. Dirac cones are deformed. We investigate the effect of uniaxial strain on the radiative properties of graphene from the perspective of direction and modulus. Optical conductivity exhibits wealthy phenomenon due to the degeneracy of the energy band broken by strain. The total energy radiation exhibits a novel behavior of periodicity in θ, in accordance with the symmetry of the hexagonal honeycomb lattice.